Small-arc volumetric-modulated arc therapy: A new approach that is superior to fixed-field IMRT in optimizing dosimetric and treatment-relevant parameters for patients undergoing whole-breast irradiation following breast-conserving surgery. Issue 34 (August 2016) - Yu, Jing; Hu, Tao; Chen, Yeshan
Abstract : Abstract: Volumetric-modulated arc therapy (VMAT) is considered to deliver a better dose distribution and to shorten treatment time. There is a lack of research regarding breast irradiation after breast-conserving surgery (BCS) using VMAT with prone positioning. We developed a new small-arc VMAT methodology and compared it to conventional (fixed-field) intensity-modulated radiation therapy (IMRT) in the dosimetric and treatment relevant parameters for breast cancer patients in the prone position. Ten early-stage breast cancer patients were included in this exploratory study. All patients underwent computed tomography (CT) simulation scan in the prone position and for each patient, IMRT and VMAT plans were generated using the Monaco planning system. Two symmetrical partial arcs were applied in the VMAT plans. The angle ranges of the 2 arcs were set to approximately 60° to 100° and 220° to 260°, with small adjustments to maximize target coverage, while minimizing lung and heart exposure. The IMRT plans used 4 fixed fields. Prescribed doses were 50 Gy in 25 fractions. The target coverage, homogeneity, conformity, dose to organs at risk (OAR), treatment time, and monitor units (MU) were evaluated. Higher median conformal index (CI) and lower homogeneity index (HI) of the planning target volume (PTV) were respectively observed in VMAT and plans group (CI, 95% vs 91%; HI, 0.09 vs 0.12; P < 0.001). The volumes of ipsilateral lung receiving 30, 20, 10, and 5 Gy were lower for VMAT ( P < 0.01), being 10%, 14.9%, 25.9%, and 44.9%, respectively, compared to 11.79%, 17.32%, 30.27%, and 50.58% for the IMRT plans. The mean lung dose was also reduced from 10.6 ± 1.8 to 9.6 ± 1.4 Gy ( P = 0.001). The volumes of the heart receiving 30 and 40 Gy were similar for the 2 methods. In addition, the median treatment time (161 vs 412 seconds; P < 0.001) and the mean MU (713 vs 878; P < 0.001) were lower for VMAT. Small-arc VMAT plan improved CI and HI for the target, spared the dose of lung, and reduced treatment time and MU, compared to IMRT. It is a more promising irradiation technique for post-BCS radiotherapy.